2016
DOI: 10.15517/am.v27i2.24386
|View full text |Cite
|
Sign up to set email alerts
|

Ácidos grasos, fermentación ruminal y producción de metano, de forrajes de silvopasturas intensivas con Leucaena.

Abstract: <p><span>El objetivo del presente trabajo fue determinar el efecto de los forrajes sobre los ácidos grasos de cadena larga, fermentación ruminal y producción de metano de un sistema silvopastoril intensivo de </span><em>Leucaena leucocephala</em><span>. La investigación se desarrolló en el laboratorio NUTRILAB–GRICA, perteneciente a la Facultad de Ciencias Agrarias, de la Universidad de Antioquia, Medellín–Colombia, en julio del 2013. Se utilizó la técnica de producción de g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
2
0
1
Order By: Relevance
“…In ruminants, trans fatty acids are produced by bio-hydrogenation of linoleic and linolenic acids in the rumen and, in consequence, may appear in milk or dairy products (Sommerfeld, 1983). Prieto-Manrique et al (2016) reported that linoleic and linolenic acids were both increased in the diet and digesta with a dietary inclusion of 14 % of L. leucocephala. Clinical studies have suggested that trans fatty acids, particularly C18:1, increase the risk of coronary heart disease (Precht and Molkentin, 2000); however, Meijer et al (2001) reported that diets high in elaidic acid did not increase blood cholesterol levels in hamsters.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In ruminants, trans fatty acids are produced by bio-hydrogenation of linoleic and linolenic acids in the rumen and, in consequence, may appear in milk or dairy products (Sommerfeld, 1983). Prieto-Manrique et al (2016) reported that linoleic and linolenic acids were both increased in the diet and digesta with a dietary inclusion of 14 % of L. leucocephala. Clinical studies have suggested that trans fatty acids, particularly C18:1, increase the risk of coronary heart disease (Precht and Molkentin, 2000); however, Meijer et al (2001) reported that diets high in elaidic acid did not increase blood cholesterol levels in hamsters.…”
Section: Resultsmentioning
confidence: 99%
“…Gamma linolenic acid is a polyunsaturated long-chain fatty acid which is produced in the body from linoleic acid by the enzyme delta-6-desaturase (Kapoor and Huang, 2006). Those results could have been effect of a higher supply of linoleic and linolenic acids coming from the Leucaena fodder (Prieto-Manrique et al, 2016) and probably due to seasonal differences in consumption of this legume. These fatty acids contribute with the total content of omega-6 fatty acids which were significantly higher (P<0.05) in cheese from ISS (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Estudios con mayor proporción de kikuyo: botón de oro (82,5:17,5) y con suplementación energética, lograron aumentar casi 3 L de leche vaca/día, lo que puede estar sustentado en una mejora del balance energético-proteico (Cardona-Iglesias et al, 2017). Otras investigaciones se han enfocado en mejorar el perfil lipídico de la leche, que se puede perfilar como un alimento funcional para los humanos (Mahecha et al, 2008;Prieto-Manrique et al, 2016). Hay más trabajos publicados sobre esta temática en el trópico bajo (≤1500 m s. n. m.) con sistemas de producción de doble propósito o lechería tropical (Barragán Hernández et al, 2016).…”
Section: Introductionunclassified